1999
DOI: 10.1017/s0140525x99371788
|View full text |Cite
|
Sign up to set email alerts
|

Good interactions are hard to find

Abstract: Caplan & Waters's arguments for separate working memory subsystems for “interpretive” and “post-interpretive” comprehension processes do not have a solid empirical basis. The likely involvement of a separate phonological loop makes their memory-load data irrelevant to theory evaluation, and the lack of statistical power from nonoptimal experimental designs and analyses unfairly reduces the chances of detecting the relevant interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The visual digit load also adds nothing to the effects of noise or speech compression, except for (paradoxically) a slight increase in overall accuracy when digits are added to noise. Because the digit task has played an important role in the debate between Caplan and Waters (1999) and Just and Carpenter (1992) and Miyake et al, (1999), we return to these somewhat counterintuitive results for digits in more detail in the final discussion.…”
Section: Experiments 1b: College Students Under Normal and Stress Condmentioning
confidence: 98%
“…The visual digit load also adds nothing to the effects of noise or speech compression, except for (paradoxically) a slight increase in overall accuracy when digits are added to noise. Because the digit task has played an important role in the debate between Caplan and Waters (1999) and Just and Carpenter (1992) and Miyake et al, (1999), we return to these somewhat counterintuitive results for digits in more detail in the final discussion.…”
Section: Experiments 1b: College Students Under Normal and Stress Condmentioning
confidence: 98%
“…Our expectation was that more continuous scoring methods would have better distribution and reliability characteristics because they provide more discrimination in terms of individual differences (Miyake, Emerson, & Friedman, 1999). Although the distribution characteristics (i.e., normality tests, skewness, and kurtosis) for span measures are rarely reported, there are a few studies that have reported reliability for various working memory span measures.…”
mentioning
confidence: 99%
“…A factor that may affect the reliability and stability of WM measures is the method used to score the task. Miyake, Emerson, and Friedman (1999) have claimed that highly discrete measures of individual differences, such as the traditional reading span scores, are nonoptimal and result in low statistical power, since they reduce variance by not capturing subtle differences that may exist among individuals. In addition, they pointed out that the division of subjects into WM span groups raises problems, because this method treats all the members of a group as identical and so reduces power.…”
mentioning
confidence: 99%